2016
DOI: 10.11118/actaun201664031037
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility in Food Manufacturing Companies - Environmental Dimensions

Abstract: The degree of a company’s acceptance and integration of the CSR concept is directly reflected in the fundamental principles of the company. Through the environmental sustainability, a company can make a positive contribution to the society and the natural environment. Competitive and cost pressures are the key drivers of sustainable development in the industry. Today, many international food and drink companies are delivering excellent achievements. The present paper tries to highlight how much are food manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…But on the other side, it creates social capital, which strengthens interpersonal relationships and cooperation (Hintošová, 2010). On the one hand, some authors confirmed that the CSR concept became very important for the society based on research of Ambramuszkinová -Pavlíková and Basovníková, 2014), on the other hand, (Egerová et al, 2013) and (Nagyová et al, 2016) described that the corporate social responsibility included the economic, legal, ethical, and philanthropic expectations, which had a big influence on the development of companies and their activities. At present, the principles of responsible business are acquired by more and more companies.…”
Section: Literature Reviewmentioning
confidence: 89%
“…But on the other side, it creates social capital, which strengthens interpersonal relationships and cooperation (Hintošová, 2010). On the one hand, some authors confirmed that the CSR concept became very important for the society based on research of Ambramuszkinová -Pavlíková and Basovníková, 2014), on the other hand, (Egerová et al, 2013) and (Nagyová et al, 2016) described that the corporate social responsibility included the economic, legal, ethical, and philanthropic expectations, which had a big influence on the development of companies and their activities. At present, the principles of responsible business are acquired by more and more companies.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Environmental sustainability can help a company make a positive contribution to society and the natural environment (Nagyová et al, 2016). The environment has become a part of a company's responsible approach to business activity and, at the same time, an opportunity for entrepreneurial growth (Carroll, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Milk consumption has a positive impact on human health, growth and development of the human body (Košičiarová et al, 2017), strengthening of cognitive processes, health protection and prevention of various diseases (The Dairy Council, 2014). Despite the positive effects, it is necessary to solve the problem due to their inadequate consumption, which has been below the recommended intake in recent years (Nagyová et al, 2016). However, an individual satisfaction in food consumption depends more on the social and institutional context (Cecchini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%